Tüketicinin korunması hakkında kanun çerçevesinde ayıplı hizmetten sorumluluk - Doğan, Yasemin (My University, 2020)
6502 sayılı Tüketicinin Korunması Hakkında Kanun’un 13 ile 16. maddeleri arasında ayıplı hizmetten sorumluluğa ilişkin hükümler yer almaktadır. Tüketicinin Korunması Hakkında Kanun kapsamında, Türk Borçlar Kanunu’ndan farklı bir şekilde, sözleşmenin konusunun mal veya hizmet olmasına göre ayırım yapılarak, ayıplı hizmetten sorumluluk hükümleri bu ayırıma özgü olarak düzenlenmiştir. Hizmet sözleşmesi, mal sağlama taahhüdü dışında tüm sözleşme türlerini kapsamaktadır. Tüketicinin Korunması Hakkında Kanun m. 13 çerçevesinde düzenlenen ayıplı hizmet kavramı, ayıplı ifanın yanı sıra sözleşmenin süresi içinde başlamaması ve özen eksikliğini de içeren hizmetin objektif olarak sahip olarak sahip olması gereken özellikleri taşımamasıdır. Tüketicinin Korunması Hakkında Kanun kapsamında hizmet sözleşmesi olarak kabul edilen eser sözleşmesi, vekâlet sözleşmesi gibi tüm sözleşme türlerinin niteliğine uygun düştüğü ölçüde ayıplı hizmetten sorumluluk hükümleri uygulama alanı bulur.

The articles 13 and 16 in the law on Consumer Protection-No. 6502. include the provisions on liability for defective service. In the law on Consumer Protection, unlike the Turkish Code of Obligations, the provisions on liability for defective services are regulated in accordance with the discrimination according to whether the subject of the contract is goods or services. The service contract covers all types of contracts except the commitment to provide goods. According to the Law on Consumer Protection article 13, the concept of a defective service organized within the framework of a defective performance, as well as the fact that it does not start within the term of the contract and does not carry the characteristics that the service should have objectively, including a lack of care. Within the scope of the law on Consumer Protection, the independent contractor agreement, which is considered as a contract of service, finds the field of application of defective service liability provisions to the extent of its accordance with the nature of all types of contracts, such as a contract of mandate.
Keywords: Ayıplı Hizmet; Civil law; Compensation; Consumer Contract; Defective Service; Medeni hukuk; Provider; Sağlayıcı; Seçimlik Haklar; Selective Rights; Tazminat Consumer; Tüketici; Tüketici Sözleşmesi